PENGARUH PEMBERIAN LIMBAH CAIR PABRIK KELAPA SAWIT TERHADAP BEBERAPA SIFAT KIMIA TANAH DAN PERTUMBUHAN BIBIT KELAPA SAWIT PADA PEMBIBITAN UTAMA: The Influence of Liquid Oil Palm Factory Waste on Some Soil Chemical Properties and Growth of Oil Palm Seeds on Main Breeding - Restu Ramadhan; Gindo Tampubolon; Ermadani Ermadani (Fakultas Kehutanan Universitas Jambi, 2021)
This research was carried out with the aim of examining the effect of providing palm oil mill effluent (LCPKS) on several soil chemical properties (pH, C-organic, and CEC) and the growth of oil palm seedlings in the main nursery. The research was conducted for 5 months, starting from March 6, 2020 to August 15, 2020 in the main nursery area for oil palm plantation companies, Belanti Jaya Village, Mersam District, Batanghari Regency, Jambi Province. The research was conducted using a Complete Acaka Design (CRD) based on the age and height of the oil palm seedlings that were uniform. The treatments used were based on the POME dosage, namely 0 L, 4 L, 5 L, 6.6 L, 10 L, and 20 L POME given every week for 20 months. Each treatment was repeated 4 times so that 24 experimental units were obtained and each unit consisted of 4 oil palm seeds so that the total number of seeds used in the study was 96 oil palm seeds. In the maintenance of seedlings, inorganic fertilizers were also given using compound fertilizers, namely NPKMg 15: 15: 16: 4, NPKMg 12: 12: 17: 2, and kiserit. The results showed that POME could increase pH from acidic to slightly acidic to neutral, C-organic from very low to moderate to very high conditions, but it could not increase soil CEC. The highest increase in pH and C-organic occurred in the 20 liter POME treatment. The provision of POME was able to increase height increase, increase in stem diameter, increase in the number of leaves, shoot dry weight, dry weight of the roots of the roots, and be able to provide an index of seed strength so that the seeds were able to be transferred to the field with seedlings of 9 months. The highest increase in oil palm seedling growth occurred in the 4 liter POME treatment.